Social Support, Self-Regulation, and Psychological Skill Use in E-Athletes - Trotter, Michael G.; Coulter, Tristan J.; Davis, Paul A.; Poulus, Dylan R.; Polman, Remco (Frontiers in Psychology, 2021)
The aims of the present study were twofold. First, to investigate self-reported social support, self-regulation, and psychological skill use in esports athletes (e-athletes) compared to traditional athletes. Second, to determine if self-reported social support, self-regulation, and psychological skill use influenced e-athlete in-game rank. An online survey was used to collect data from an international sample of e-athletes (n = 1,444). The e-athletes reported less social support, self-regulation, and psychological skill use than reported by traditional athletes in previous studies. E-athletes with higher scores in social support, self-regulation, and psychological skill use was associated with higher in-game rank. The lack of an organisational structure in esports may be a contributing factor as to why e-athletes score lower than traditional athletes on social support, self-regulation, and psychological skill use. Future research is warranted to explore the development of esports programs aiming to promote athletes’ social support, self-regulation, and use of psychological skills to enhance in-game performance and well-being.